2006
DOI: 10.1152/physiolgenomics.00036.2006
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition prepartum alters hepatic gene expression and function in dairy cows as assessed by longitudinal transcript and metabolic profiling

Abstract: Liver metabolism and health in dairy cows during the periparturient period are affected by plane of nutrition prepartum. Long-term adaptations in hepatic gene expression are important for complete understanding of liver function. We examined temporal gene expression profiles during the dry period and early lactation in liver of Holstein cows fed moderate dietary energy ad libitum or restricted during the entire dry period using a microarray consisting of 7,872 annotated cattle cDNA inserts and quantitative RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
191
6
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(222 citation statements)
references
References 49 publications
21
191
6
4
Order By: Relevance
“…Underlying these differences in performance are different patterns of endocrine profiles (Drackley et al, 2001;Gong et al, 2002;Lucy et al, 2009). Clearly, these differences are underpinned by differences in gene expression and enzyme profiles (Loor et al, 2006;Sumner-Thomson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Underlying these differences in performance are different patterns of endocrine profiles (Drackley et al, 2001;Gong et al, 2002;Lucy et al, 2009). Clearly, these differences are underpinned by differences in gene expression and enzyme profiles (Loor et al, 2006;Sumner-Thomson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The functional analysis of the clusters in the data set of Loor et al (2005) and Loor et al (2006) identified several overrepresented functions (Loor et al, 2011). Among the responses observed it was evident that clusters characterized by a strong downregulation in both overfed and restricted-fed v. control cows were overrepresented with terms related to induction of inflammation, suggesting that both management approaches led to downregulation of genes involved in the inflammatory response and in particular the complement pathway (Loor et al, 2011).…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 97%
“…However, because restricted-energy fed cows did not experience fatty liver relative to energy-overfed cows (Loor et al, 2006) it is apparent that different signals are capable of triggering the same metabolic adaptations in liver, for example, cows with severe nutrition-induced ketosis early postpartum also upregulate fatty acid catabolism pathways in liver (Loor et al, 2007). A novel observation in cows fed restrictedenergy prepartum was the enrichment of antigen processing and presentation pathways enriched in a cluster of clearly upregulated genes.…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
“…Then, the use of cannulation techniques was used to measure nutrient flow from the digestive tract. The apparent absorption of nutrients into the portal vein and the use of nutrients by the major organs and tissues were then quantified with the help of multicatheterisation techniques on live animals, with the combination of the blood flow measurement with venous-arterial differences and nutrient labelling techniques providing a better understanding of nutrient fate within the body and within tissues (Drackley et al, 2006). In parallel, the development of in vitro (tissue or cell culture) and ex vivo (enzyme activities, gene expression) approaches has provided knowledge about control mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overfeeding might render the cow liver more susceptible to oxidative stress and DNA damage through changes in gene expression. In other words, overfeeding predisposes cows to fat accumulation in the liver and to health problems, thereby demonstrating the importance of nutrition planning for dairy cows (Loor et al, 2006). Although these conclusions were, at least in part, previously known through physiological approaches, the global transcriptomic approach has the merit of assessing these biological adaptations by studying genes on a large scale.…”
Section: Introductionmentioning
confidence: 99%